2012
DOI: 10.2478/s11534-011-0090-8
|View full text |Cite
|
Sign up to set email alerts
|

Photoluminescence of bis(8-hydroxyquinoline) zinc (Znq2) and magnesium (Mgq2)

Abstract: Absorption and photoluminescence (PL) spectra, PL quantum efficiency, and PL lifetime have been investigated on bis(8-hydroxyquinoline) zinc (Znq2) and magnesium (Mgq2) in solutions and powder. Znq2 and Mgq2 have the lowest-energy absorption band at 376 and 396 nm in acetonitrile solution, respectively, and emission band with peak at 555 and 480 nm. The PL quantum efficiency is 0.03 and 0.45 for Znq2 and Mgq2 in the solution, respectively, while 0.45 and 0.36 in powder. Unlike the case of powders, two PL lifet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 18 publications
1
17
0
Order By: Relevance
“…Furthermore, the theoretical value of the HOMO–LUMO gap of 1 determined by DFT/TD‐DFT (3.19 eV) is close to the experimental value (3.06 eV), and it is in the range of those of [Zn(BTZ) 2 ] 2 [6b] and [Znq 2 ] 4 ,[8d], well‐established compounds in OLED fabrication (Table and Figure ).…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…Furthermore, the theoretical value of the HOMO–LUMO gap of 1 determined by DFT/TD‐DFT (3.19 eV) is close to the experimental value (3.06 eV), and it is in the range of those of [Zn(BTZ) 2 ] 2 [6b] and [Znq 2 ] 4 ,[8d], well‐established compounds in OLED fabrication (Table and Figure ).…”
Section: Resultssupporting
confidence: 74%
“…The electrochemical and photophysical data for 1 are tabulated in Table , together with experimental data for [Zn(BTZ) 2 ] 2 [6a], [6b], [6d] and [Znq 2 ] 4 ,[8d], molecular luminescent materials which have been successfully used in OLEDs. Cyclic voltammetry measurements for 1 in DCM show two irreversible ligand‐based oxidation events at 0.97 V and 1.16 V vs. SCE.…”
Section: Resultsmentioning
confidence: 99%
“…As a result, a fluorescent species under study can be identified by its emission spectrum and emission lifetime ( τ f ), and these can be used for discrimination of the autofluorescence background . Further, τ f can report on the microenvironment surrounding the fluorescent species and its kinetics, including fluctuations in viscosity or pH, binding to additional complex molecules, or depletion of the excited state due to the proximity of neighboring particles . We found that Zn(PT) 2 exhibits photoluminescence (PL) features, which can be used to improve its imaging contrast.…”
Section: Introductionmentioning
confidence: 99%
“…8‐Hydroxyquinoline bivalent metal complex (MQ 2 ) is an attractive kind of luminescent material, which has broad application prospects . MQ 2 (for example, 8‐hydroxyquinoline Barium, 8‐hydroxyquinoline magnesium, 8‐hydroxyquinoline calcium, and 8‐hydroxyquinoline zinc) has many advantages, such as simple synthesis conditions, high luminous efficiency, and high thermal stability . Many scholars have done in‐depth research focused on extending application potential of MQ 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Another disadvantage of liquid‐phase method is low yield . The disadvantage is that MQ 2 can only be excited under ultraviolet light by liquid‐phase method . This spends a massive amount of energy and severely limits the scope of application of MQ 2 .…”
Section: Introductionmentioning
confidence: 99%